The Relationship between Administrative Skills and Administration According to Implementation Standard of Leader in Child Development Centers under Local Administrative Organization in Lopburi Province - Srisuk, Jatuphat (Ratchaphruek Journal, 2021)
This quantitative research aimed: 1) to study the level of administrative skills of heads of child development centers under local administrative organization in Lopburi province; 2) to study the administrative level according to the implementation standard of child development centers under local administrative organization; and 3) to study the relationship between administrative skills and the administration according to the implementation standard of child development centers under local administrative organization in Lopburi province. Samples were 226 leaders and teachers of child development centers under local administrative organization in Lopburi Province. The instrument used was the questionnaire with five-level which the reliability was 0.96. Data were analyzed by frequency, percentage, mean, standard deviation, and Pearson product-moment correlation coefficient. The results found that: 1) The administrative skills, the overall, were found at the high level ( = 4.44). For the Individual aspects, the highest average were conceptual aspects at a high level ( = 4.47) followed by technical a high level ( = 4.44) and human relations at a high level ( = 4.43) respectively; 2) The administration according to the implementation standard of child development centers was found at a high level ( = 4.37). 3) The relationship between administrative skills and the administration according to the implementation standard of child development centers under local administrative organization in Lopburi province, the overall had correlation coefficient (r) between 0.56-0.88 at moderate level to high level, statistically significant at .01 level.